Effect of cooking and storage temperature on resistant starch in commonly consumed Indian wheat products and its effect upon blood glucose level - Kaur, Prabhjot; Kaur, Harpreet; Aggarwal, Renuka; Bains, Kiran; Mahal, Amrit Kaur; Gupta, O. P; Singla, Lachhman Das; Singh, Kulvinder (Frontiers in Nutrition, 2023)
This study was conducted to evaluate the effect of cooking and storage temperature on the formation of resistant starch in Indian wheat products and its effect upon blood glucose level in humans and rats. Wheat products were prepared by common cooking methods roasting (Chapati), boiling (Dalia), Shallow frying (Paratha) and Deep frying (Poori) and then stored at different temperatures including freshly prepared with in 1h(T1), stored for 24 h at room temperature (20-22⁰C)(T2), kept at 40C for 24 h(T3) and reheated after storing at 40C for 24 h(T4). The products were then analyzed for proximate composition (moisture, crude protein, crude fat, ash crude fibre and carbohydrates). Effect of different cooking methods and storage temperatures on Resistant, non resistant and total starch, total dietary fibre (soluble and insoluble), in vitro starch digestion rate (rapidly and slowly digestible starch), amylose and amylopectin content were analyzed using standard operating procedures. Glycemic index and glycemic load of wheat products were also analyzed. Further, the effect of resistant starch rich chapati on blood glucose level of rats was also studied. Tukey’s test in factorial CRD was used to assess the effect of cooking and temperature on various parameters. The amount of resistant starch found high in dalia (boiling, 7.74%), followed by parantha (shallow frying, 4.94%), chapati (roasting, 2.77%) and poori (deep frying 2.47%). Under different storage temperatures it was found high in products stored at 4ᵒC (T3), followed by products stored at room temperature (T2), reheated products (T4) and lesser in freshly prepared products (T1). The glycemic index and glycemic load was found low in chapati (43, 32.3) and dalia (41.1, 28.6) stored at 4ᵒC (T3) compared to others. The resistant starch content found in chapati stored at T3 found more effective to reduce blood glucose level in rats from 291.0 mg/100ml to 225.2mg/100ml in 28 days of study compared to freshly prepared chapati (T1) and stored at room temperature (T2). At 4⁰C stored products has high amount of insoluble dietary fibre, slowly digestible starch, high amylose and low glycemic index. They take time to digest. Hence, slowly increase in blood glucose levels.